Tungsten dust remobilization under steady-state and transient plasma conditions. (August 2017) - Ratynskaia, S.; Tolias, P.; De Angeli, M.; Weinzettl, V.; Matejicek, J.; Bykov, I.; Rudakov, D.L.; Vignitchouk, L.; Thorén, E.; Riva, G.; Ripamonti, D.; Morgan, T.; et al.
Highlights: Review of experiments and modelling of dust remobilization in fusion plasmas. Steady state remobilization: competition between plasma-induced and contact forces. Transient plasma remobilization: heat transfer aspects become dominant. Adhesion has a central role and surface roughness adds a probabilistic component. Wetting-induced coagulation in clusters as an adhered dust growth mechanism. Abstract: Remobilization is one of the most prominent unresolved fusion dust-relevant issues, strongly related to the lifetime of dust in plasma-wetted regions, the survivability of dust on hot plasma-facing surfaces and the formation of dust accumulation sites. A systematic cross-machine study has been initiated to investigate the remobilization of tungsten micron-size dust from tungsten surfaces implementing a newly developed technique based on controlled pre-adhesion by gas dynamics methods. It has been utilized in a number of devices and has provided new insights on remobilization under steady-state and transient conditions. The experiments are interpreted with contact mechanics theory and heat conduction models.